Radical scavenging capacity, antibacterial activity, and quantum chemical aspects of the spectrophotometrically investigated iridium (III) complex with benzopyran derivative - Mohmad, Masrat; Agnihotri, Nivedita; Kumar, Vikas; Azam, Mohammad; Wabaidur, Saikh Mohammad; Kamal, Raj; Kumar, Rakesh; Alam, Mahboob; Kaviani, Sadegh (Frontiers in Pharmacology, 2022)
An explicit aqueous phase spectrophotometric study concerning the determination of iridium (III) in traces by its reaction with benzopyran derived chromogenic reagent, 6-chloro-3-hydroxy-7- methyl-2-(2’-thienyl)-4-oxo-4H-1-benzopyran (CHMTB) is performed. The complexing reagent instantly forms a yellow complex with Ir(III) at pH 4.63. In the complex, metal is bound to ligand in a ratio 1:2 as ascertained by Job’s continuous variations, mole ratio and equilibrium shift methods. The complex absorbs maximally at 413-420 nm retaining its stability up to 4 days. Optimum set of conditions has been set with respect to the parameters governing formation of the stable complex and under the set optimal conditions, the Ir(III)-CHMTB complex coheres to Beer’s law between 0.0-1.5 µg Ir(III) mL-1. The extinction coefficient and Sandell’s sensitivity are 1.18×105 L mol-1 cm 1 and 0.00162 µg cm-2 at 415 nm, respectively. The correlation coefficient (r) and standard deviation (SD) were 0.9999 and ± 0.001095, respectively while the detection limit as analysed was 0.007437 µg mL-1. Interference with respect to analytically important cations and complexing agents has been studied thoroughly and it is found that majority of the ions/agents do not intervene information of the complex thus adding to versatility of the method. The results obtained from aforesaid studies are indicative of simple, fast, convenient, sensitive, and versatile method for microgram analysis of iridium (III) using CHMTB as a binding ligand. Further, the studied complex is subjected to the evaluation of antibacterial and antioxidant capacity by employing Agar Diffusion assay and DPPH.radical scavenging method, respectively. The results obtained from the mentioned assays reveal that the complex has a significant potency to act as an antibacterial and antioxidant agent. Finally, the computational approach through DFT of the formed complex confirmed the associated electronic properties of the studied complex.